Instagram's Role in Inducing Event-Related Social Anxiety for Public Engagement - Helen Fransisca; Rizaldi Parani (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2023)
This study aims to illustrate the social anxiety occurring on the Instagram, which creates social influence among individuals regarding entertainment events. This is closely related to the desire of community members to attend Coldplay concerts in Indonesia and neighbouring countries such as Malaysia, the Philippines, Singapore, and Thailand. Therefore, the research question raised is